Experiences of peer navigators implementing a bilingual multilevel intervention to address sexually transmitted infection and HIV disparities and social determinants of health - José A. Robles Arvizu; Lilli Mann‐Jackson; Jorge Alonzo; Manuel Garcia; Lucero Refugio Aviles; Benjamin D. Smart; Scott D. Rhodes (Wiley, 2023)
Abstract Introduction Sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) disproportionately affect young gay, bisexual and other men who have sex with men (GBMSM) and transgender women of colour. We explored the experiences of community‐based peer navigators ('Community Navigators') who participated in Impact Triad, a bilingual multilevel intervention developed by our community‐based participatory research partnership to reduce STIs and HIV and address social determinants of health (e.g., employment, education, social support and discrimination) among young GBMSM and transgender women of colour. Methods Individual in‐depth interviews were conducted with 15 Community Navigators who participated in Impact Triad. Themes were identified through constant comparison. Results Community Navigators' mean age was 31.4 years. Seven were self‐identified as African American/Black, 5 as Latine, 2 as multiracial/multiethnic, 1 as Asian American, 10 as cisgender men, 4 as transgender women and 1 as gender nonbinary. Thirteen themes emerged in three domains: (1) key aspects of the Community Navigator role (e.g., desire to serve as a community resource, the importance of being part of the communities in which one was working, the value of having an official role, being connected to other Community Navigators to problem‐solving and sustaining intervention aspects long‐term); (2) experiences implementing Impact Triad (e.g., engaging community members, meeting prioritized needs, building trust, using social media, increasing awareness and knowledge and challenges related to COVID‐19) and (3) lessons learned for future interventions (e.g., facilitating access to broader resources, building additional skills and increasing interactions among Community Navigators). Conclusion Interviews identified important learnings about serving as Community Navigators and implementing Impact Triad that can guide future efforts to address STI/HIV disparities and social determinants of health through community‐based peer navigation. Patient or Public Contribution Throughout this intervention trial, our partnership worked collaboratively with a study‐specific community advisory board (CAB) comprised primarily of young GBMSM and transgender women of colour. Members of this CAB participated in all aspects of the trial including trial design, intervention development, recruitment and retention strategies, data collection and analysis, interpretation of findings and dissemination.